2013
DOI: 10.1089/apc.2013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Is Self-Perceived HIV Risk Congruent with Reported HIV Risk Among Traditionally Lower HIV Risk and Prevalence Adult Emergency Department Patients? Implications for HIV Testing

Abstract: Because reliance on patients' self-perceived risk for HIV might mislead emergency department (ED) clinicians on the need for HIV testing, we aimed to measure congruency between self-perceived and reported HIV risk in a traditional lower prevalence, lower-risk cohort. A random sample of 18-to 64-year-old patients at a large academic urban ED who were by self-report not men-who-have-sex-with-men (MSM) or injection-drug users (IDUs) were surveyed regarding their self-perceived and reported HIV risk. Sixty-two per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 66 publications
1
44
1
Order By: Relevance
“…29 However, despite disclosing HIV risk behaviours, some patients still perceive themselves to be low risk. 30,12 In the older population, this low perceived risk may be exacerbated by the perception HIV is a young person's disease. 17 Despite public opinion, evidence shows that many older people remain sexually active; one study indicated the main reason for lack of sex in this group may be physical limitations, not because of lack of desire or opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, despite disclosing HIV risk behaviours, some patients still perceive themselves to be low risk. 30,12 In the older population, this low perceived risk may be exacerbated by the perception HIV is a young person's disease. 17 Despite public opinion, evidence shows that many older people remain sexually active; one study indicated the main reason for lack of sex in this group may be physical limitations, not because of lack of desire or opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…In considering clinical implications of these findings, it is important for health care providers to be aware of potential ‘incongruence’ between perception and behaviour. For example, if providers rely on patient’s self-perceived risk without assessing behaviour directly, they may miss opportunities to provide appropriate testing or counselling (Pringle, Merchant, & Clark, 2013). While results indicate strong interest in PrEP, further programmatic and implementation research is needed to understand women’s ability to successfully adhere to PrEP, and optimize the role of family planning clinics in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous variables such as age were dichotomized at the median value. Information on current sexual behaviour, including location for soliciting sexual partners, history of transactional sex, number of sexual partners, alcohol and drug use, frequency of condom use and willingness to discuss HIV/AIDS with a sexual partner, was used to ascertain a "calculated risk score" for each respondent [26,27].…”
Section: Descriptive Analysismentioning
confidence: 99%